Gravity wave momentum flux in the mesosphere measured by VHF radar at Davis, Antarctica - Peter Love; Murphy, DJ (2016)
Polar mesospheric summer echoes observed in VHF MST radar measurements at Davis, Antarctica 68.5°S, 78.0°E, are used to measure high-frequency gravity wave momentum flux in the vicinity of the mesopause during the Southern Hemisphere summer of 2014–2015. The momentum flux spectrum is generally isotropic with a slight bias in the seasonal mean toward the southeast. Zonal and meridional components of the seasonal mean momentum flux are an order of magnitude smaller than the absolute momentum flux. Diurnal and semidiurnal modulation of the momentum flux correspond to perturbations of the seasonal mean winds by atmospheric tides. Quantitative measures of gravity wave intermittency yield high values and increase with altitude through the mesopause region. These intermittency characteristics are attributed to the increase with altitude of wind variability through the mesopause region as a result of the tides.